Relationship between indicators of internal aggression and age categories of athletes in the context of the problem of moral verbality in sports - Skrygin S.V.; Yurchenko A.L.; Galochkin P.V.; Anurov V.L. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the dominant aggressiveness of various age categories of athletes as a potential factor in their asocialization. Methods and structure of the study. 36 former athletes (2 international masters of sports, 13 masters of sports, 12 candidates for master of sports, 9 first-class athletes) of various age categories took part in the scientific work. Based on a questionnaire survey (questionnaire by L.G. Pochebut), the magnitude of aggression was determined and its direction was assessed. Results and conclusions. Based on the data obtained, a hypothesis was formulated about the cause-and-effect relationship between the age of former and current athletes and physical and verbal aggression. No statistically significant connections were found between the age of athletes and emotional and objective aggression. To compensate for the effect of the factor of verbal aggression in the process of socialization of active athletes, the authors proposed a method of socio-psychological mentoring, which is based on coaching pedagogical cultivation of positive verbality and control over the acquisition of positive social experience.